Respuestas

  • Usuario de Brainly
2014-02-07T01:37:46+01:00
1) => (-4/3)^(-2) - (4/6)^(-1) = 1/ (-4/3)^2 -  1/ (2/3)^(1) = 1 / (16/9) - 1 / (2/3)
............................................................................= 9 / 16 - 3 / 2
........................................................................... = (9 x 2 - 3 x 16) / ( 16 x 2)
........................................................................... = ( 18 - 48) / 32
..........................................................................  = - 30 / 32
.......................................................................... = - 15/16 ------ Respuesta:
...........................____
2) => (- 1/2)^(2) - V(4/9) =  (-1/2)^2 - 2/3
................................... =  1/4 - 2/3
................................... = ( 1x3 - 2x4) / (4x3)
................................... = ( 3 - 8) / 12
................................... = - 5 / 12 ------------- Respuesta.

3) {-1/2 (4/5)} / (5/3) + (-1/2) = { - 2/5 }/ (5/3) - 1/2
....................................... = - 6/25 - 1/2
...................................... = (-12 - 25) / 50
...................................... = - 37/50 .--------------- Respuesta.

Suerte. Santiagopr99
gracias me ayudaste mucho te tomates tu tiempo tienes tus 5 estrellas